2017
DOI: 10.2463/mrms.mp.2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spatial Resolution in Three-dimensional Cine Phase Contrast Magnetic Resonance Imaging on the Accuracy of Hemodynamic Analysis

Abstract: Introduction:We aim to elucidate the effect of spatial resolution of three-dimensional cine phase contrast magnetic resonance (3D cine PC MR) imaging on the accuracy of the blood flow analysis, and examine the optimal setting for spatial resolution using flow phantoms.Materials and Methods:The flow phantom has five types of acrylic pipes that represent human blood vessels (inner diameters: 15, 12, 9, 6, and 3 mm). The pipes were fixed with 1% agarose containing 0.025 mol/L gadolinium contrast agent. A blood-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Previously published paper reported that the error rate of the maximum velocity is less than 10% when the ratio of the pixel size to the inner diameter is less than 10%. 16 In this experiment, the voxel size was 10% of the diameter (voxel size, 0.7 mm; diameter, 7 mm), but the error of the maximum velocities of some scanners exceeded 10%. It is estimated that the measurement error of the maximum flow velocity would be less than 10% if we had used optimum conditions including imaging parameters, receiver coil, imaging position, and so on.…”
Section: Discussionmentioning
confidence: 77%
“…Previously published paper reported that the error rate of the maximum velocity is less than 10% when the ratio of the pixel size to the inner diameter is less than 10%. 16 In this experiment, the voxel size was 10% of the diameter (voxel size, 0.7 mm; diameter, 7 mm), but the error of the maximum velocities of some scanners exceeded 10%. It is estimated that the measurement error of the maximum flow velocity would be less than 10% if we had used optimum conditions including imaging parameters, receiver coil, imaging position, and so on.…”
Section: Discussionmentioning
confidence: 77%
“…However, it was greater than 40% for a pixel size of 1.0 mm. 29 As the standard spatial resolution for current 4D flow MRI is around 1.0 mm, errors of 20%-40% should be taken into account in the flowmetry of tiny vessels.…”
Section: D Flow Mri For Abdominal Aortamentioning
confidence: 99%
“…On the other hand, MRFD needs lesser time and personnel effort despite its low resolution compared with CFD in assessing arteries with small caliber. 32 It is reflected that MRFD is more feasible in the clinical setting whereas CFD would be appropriate for the experimental and research setting. In the present study, the statistically significant hemodynamic biomarkers between the ruptured and unruptured groups showed the same pattern in both MRFD and CFD-based results.…”
Section: Discussionmentioning
confidence: 99%